Development of Interactive Context-Based Learning Multimedia to Improve Students' Understanding of Payment Systems and Instruments - Erda Erlina Putri; Muhammad Abdul Ghofur (Darul Yasin Al Sys, 2026)
This research was motivated by students' low understanding of the topic of payment systems and payment instruments due to its complex and abstract nature, as well as the use of instructional media that has not been able to effectively visualize concepts and promote active student engagement. This research aimed to develop feasible contextual-based interactive learning multimedia on the topic of payment systems and payment instruments and to determine the improvement in students' understanding after using the developed multimedia. The method used was Research and Development (R&D) employing the 4D development model (Define, Design, Develop, Disseminate), which was limited to the Development stage. A limited trial was conducted on 25 students of Class X-7 at SMA Negeri Bareng using a One-Group Pretest-Posttest design. The results showed that the developed contextual-based interactive learning multimedia was categorized as highly feasible, with feasibility percentages of 81.17% from the media expert, 83.07% from the subject matter expert, and 82.22% from the language expert. The Wilcoxon Signed-Rank Test yielded a significance value of 0.000 (p < 0.05), indicating a significant difference between the pretest and posttest scores. In addition, the N-Gain analysis produced an average score of 0.7560 (75.60%), which was categorized as high. Based on these findings, the contextual-based interactive learning multimedia was declared highly feasible and effective in improving students' understanding of the topic of payment systems and payment instruments.